Tax Morale vs Voluntary Tax Compliance with A Bibliometric Analysis Framework - Andriani, Sri; Al Idrus, Salim; Djalaluddin, Ahmad (Accounting Study Programme Faculty of Economics and Business Universitas Negeri Surabaya, 2025)
Introduction/ Main Objectives: The objectives of this study is to explain the research progress and technology trends of AD, this study presents a bibliometric analysis. Research Background: The Indonesian government's 2020 revenue target is IDR 2,233.2 trillion, with IDR 1,865.7 trillion (83.54%) coming from taxes. In 2020, Indonesia changed the structure of the State Budget by refocusing and reallocating the budget to handle the spread of Covid-19, reaching IDR 3.37 trillion. Method: This study uses meta-analysis by reviewing and synthesizing various empirical research findings from 1998 to 2021, discussing the influence of determinants on tax compliance and tax evasion. These determinants include audits, tax rates, tax sanctions, services, public trust, personal norms, social norms, and religiosity. Results: The results of this meta-analysis reinforce the social contract theory and the findings of previous studies, which concluded that the level of public service and trust significantly influence tax compliance and tax evasion. Based on data and empirical evidence, this study concludes robustly that when the public is well-served and believes that the tax money paid by taxpayers is being used properly by the government, the public perceives the government as fulfilling the contract between the government and its citizens. Conclusion: The results of this meta-analysis show that in addition to factors influenced or controlled by the government and tax authorities, internal taxpayer factors reflected in the fiscal psychology paradigm in the form of personal norms and religiosity significantly influence taxpayers' decisions to comply or not.